An assessment of the safety of the interior spaces of a selected public school in Marikina City - Mison, Judy Ann S.; Faustino, Johanna Victoria A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
This study aimed to assess the safety of the interior spaces of a selected public school in Marikina City. A case study method of research was utilized involving random sampling which consisted of 45 Grade 9 students who participated in a survey. Two teachers and one staff interviewed were selected based on the numbers of years they have been teaching and working in the school. In addition, five students were interviewed to find out if there are any issues on safety based on their experience within school premises. The school was assessed utilizing the Educational Facilities Manual 2010 and the Architect's Room Design Data Handbook. The interior components of the spaces focused on space planning and furniture layout, lighting and ventilation, and materials and finishes. The study revealed that the interior components are significant factors that affect the safety of the interior spaces of the school. This was evident on the accidents experienced by selected student respondents. These accidents include slipping, fainting, falling down the stairs, and books and shelves falling over the students. Based on the results, materials and finishes used in the spaces highly contribute to these accidents. Below minimum standard room dimensions were also considered as a contributing factor to accidents. Lastly, lighting and ventilation may be considered as factors that cause accidents in the different areas of the school. Findings show that the interior spaces of the school are not safe and this is caused by the inability of the school to fully comply with the guidelines provided both by Educational Facilities Manual 2010 and Architect's Room Design Data Handbook.
Submitted June 2016.
Thesis (BS Interior Design)-- University of the Philippines Diliman.
Keywords: Public schools -- Philippines -- Marikina -- Safety measures; Public schools -- Philippines -- Marikina -- Designs and plans